A multidisciplinary approach for esthetic improvement in a patient with swimmer’s dental erosion: a 5-year recall case report - Limvisitsakul, Apinya; Kuphasuk, Watcharaporn (Mahidol Dental Journal, 2024)
This study showcases a multidisciplinary digital approach for esthetic improvement in a patient with swimmer’s dental erosion, particularly focusing on a predictable workflow of surgical crown lengthening and restoration in cases of gummy smiles and upper anterior teeth erosion. The patient presented with excessive gingival display and swimmer’s erosion in the upper anterior teeth. Utilizing computer-aided design/computer-aided manufacturing (CAD/CAM) systems, a final digital outcome design was generated, serving as a diagnostic wax-up model for this patient. The determined position of the gingival margin level and the contour of the digital final restoration design information were transferred to produce a reference surgical guide for the surgical crown lengthening process. Additionally, the digital design model facilitated the fabrication of a silicone index for the direct restoration procedure. The combination of a simple direct restoration technique and surgical crown lengthening, enabled by the digital multidisciplinary approach, effectively addressed the patient’s concerns.